‘The Code of Chivalry’ as a Socio-ethical Standard - Farzaneh Bakhoda (اخلاق وحیانی, 2013)
A quick look at the world today and the expansion of the emerging mysticisms, which are at times immoral, and the growing conversion of the people to these new schools of mysticism, reveals that we live in the era of the humans’ return to spirituality, or the era of the return of spirituality to humans’ lives. It is at such times that a society’s reserves of cultural heritage would protect it, just as one’s immune system which comes in handy in the protection of one’s body against the infestations of diseases. The customs and traditions regarding the ways of ‘manliness’ and ‘chivalry’ are among such spiritual and cultural reserves of Iran and Islam which have formed a series of ethical and spiritual teachings and some kind of practical wisdom for the public and which have come to be very useful to the people in interregnum periods. The present paper seeks to identify and present the system of chivalry through reflecting on the written documents on the codes and the ways of chivalry and manliness and also by examining their remaining traditions such as the manner and conduct taught at traditional Iranian gymnasiums and the ways of the traditional Iranian athletes. This is because these traditions and customs enjoy special ethical and educational properties and principles, and have always heralded the original human and ethical values such as ‘equality’, ‘fraternity’, ‘wellbeing’, ‘justice’ and etc. And these very tenets and ethical principles provide an appropriate standard for the society.